Learning Mathematics: One Minute - Amir Zuhairi Zakaria; Haslina Hassan; Hanasrullah Halim; Wan Amirah Najwa Wan Idris; Muhammad Asyraf Abdullah Zawawi; Nur Fathihah Mansor (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
This game is made with purpose to educate student in terms of mathematical skill combined with fun adventure game. The target audience is the students should be primary-school (10-13 years old). This is an educational game and made on purpose to create a difference method to present solving a mathematical problem to the audience. The user will play a game where the character is chased by a dog and must avoid obstacles such as river. In each level of the game, the user must find a door in which they must solve the mathematical question as pass code. Successful in solving the mathematical question will bring user to another level. This game is made with 3 level and must be completed within 1 minute. This game can be used as a tool for learning. The level of mathematical questions is simple mathematical quiz, designed with objective to teach early age students.